Application of the DeLone and McLean Success Model to the SEMAIK Website: A Case Study in Central Lombok - Rozi, Fatrul; Fadli, Sofiansyah; Zaen, Mohammad Taufan Asri (JISA(Jurnal Informatika dan Sains), 2025)
In In the digital age, the use of information technology in public services, including population administration, is crucial. To facilitate access to online population services, the Population and Civil Registration Office of Central Lombok Regency provides the SEMAIK website. Nonetheless, several issues persist, particularly in system quality and service quality. System performance often becomes unstable, with the website slowing down when many users submit service requests simultaneously, while service responsiveness is also frequently delayed. These issues highlight the need for a more comprehensive evaluation of the platform. This study aims to quantitatively assess the effectiveness of the SEMAIK website using the DeLone and McLean Information System Success Model. Data were collected through questionnaires distributed to 126 respondents and analyzed using the SEM-PLS approach. The findings indicate that information quality positively influences system use but does not significantly affect user satisfaction. Meanwhile, service quality, system quality, and system use all show positive effects on user satisfaction. Additionally, although system use does not significantly contribute to net benefits, user satisfaction demonstrates a strong positive effect on net benefits. The model also meets the criteria for good model fit based on the goodness-of-fit assessment. However, the results suggest that aspects related to information quality and system use require improvement, as their effects on user satisfaction and net benefits are not yet optimal. These findings provide concrete recommendations for enhancing the SEMAIK website to ensure more effective and reliable digital public services.